Structural and physicochemical properties of nickel manganite NiMn2O4-δsynthesized by sol-gel and ultra sound assisted methods - Alburquenque, D. (2016)
In this work we present the structural, magnetic and surface characterization of the ceramic nickel manganite oxide NiMn2O4-δsynthesized by two methods: sol-gel and ultrasound-assisted sol-gel using nitrate salts as precursors. We have characterized the non-stoichiometric samples NiMn2O4-δusing different physicochemical analyses. X-ray diffraction and Rietveld refinement of the X-ray data indicated that the samples crystallize in the Fd3m space group characteristic of cubic spinel-related oxides. The specific surface area of the oxides was 1.3 m2/g (SG) and 16.3 m2/g (UASG). SEM results showed particle agglomerates of 1.05 μm (SG) and 0.85 μm (UASG). Temperature dependence magnetization measurements were performed and a ferrimagnetic transition was identified at 103 K and 105 K depending on the preparation method (SG and UASG, respectively). The observed Curie constant was found to vary from 7.4 to 7.7 cm3 K mol−1and hysteretic magnetization vs. applied field curves at different temperatures were obtained. XPS studies of these oxides reveal the presence of Ni2+, Mn2+, Mn3+and Mn4+ions at the surface. A probable ionic distribution as a function of the synthesis method is proposed.